Acute and sub-chronic toxicological evaluation of the herbal product HAD-B1 in Beagle dogs. (2021) - Song, Si-Yeon; Chang, Hyeok-Joon; Kim, Soo-Dam; Kwag, Eun-Bin; Park, So-Jung; Yoo, Hwa-Seung
Highlights: HAD-B1 is used in Korean medicine to treat lung cancer patients. The acute and Sub-chronic toxicity of HAD-B1 was evaluated in Beagle dogs. No toxicologically significant effects were found. The NOAEL was ≥2000 mg/kg/day for both genders, with no target organ effect. Abstract: HAD-B1 is a herbal formula originated from Korean Traditional Medicine that used to treat lung cancer patients. Herein we assessed acute and sub-chronic toxicity of HAD-B1 in beagle dogs. Acute study, 4 weeks dose rate finding (DRF) study and sub chronic toxicity study for 13 weeks were done by oral administration at doses of 0, 500, 1000, and 2000 mg/kg. Neither oral acute toxicity study nor DRF study showed any significant clinical signs, death, or weight changes. Based on that, a sub-chronic study for 13-weeks was performed. As a result, HAD-B1 caused a decrease of mean daily feed consumption in females, infiltration of intestinal inflammatory cells in both sexes, a significant decrease in total cholesterol (TCHO) in females, Kupffer cell hypertrophy/hyperplasia in the liver as well as dilation of the sinusoid. However, there were no significant toxic effects in the treated group compared to the control group. Therefore, the No Observed Adverse Effect Level (NOAEL) of the HAD-B1 is at least 2000 mg/kg/day when administrated orally for 13 consecutive weeks. These results demonstrate that HAD-B1 consumption is relatively non-toxic and safe for clinical usage.